Pengaruh Inovasi Produk, Gaya Hidup Sehat, dan Agama terhadap Keputusan Pembelian Makanan Vegetarian di Kalangan Konsumen Indonesia - Nicholas Evan; Iman Nuryanto (Forum Kerjasama Pendidikan Tinggi, 2026)
A greater understanding of the factors influencing vegetarian food choices is necessary due to the public's increased interest in plant-based diets. Three factors—product innovation, a healthy lifestyle, and religion—are thought to have an impact on customer purchase decisions. To find out how these three aspects work and how much they affect customers' vegetarian food choices, more research is required. This study aims to investigate how product innovation, a healthy lifestyle, and religion affect Indonesian consumers' decisions to buy vegetarian cuisine. The context for this study is the increased public interest in plant-based diets and earlier research that produced contradictory findings regarding the factors influencing vegetarian food purchasing. Quantitative data was gathered from 100 respondents using a questionnaire. The study was then conducted using partial least squares structural equation modeling (PLS-SEM). The results show that purchasing decisions are positively and significantly impacted by product innovation. On the other hand, leading a healthy lifestyle has little impact. The biggest and most powerful factor influencing shopping decisions is religion.